Feasibility Analysis of Learning Devices with the Science Environment Technology Society (SETS) Model Based on Science Literacy on the Subject of Ecosystems - Sani, Tia Hidayah; Harini, Nugrahaningsih Wahyu (FMIPA UNNES, 2021)
The purpose of this study is to describe feasibility of learning device with the SETS model based on science literacy on the subject of ecosystem. This study use the R&D method which adopts the modified ADDIE model consisting of analysis, design and development. At the analysis stage, a needs analysis and curriculum analysis are carried out to determine learning needs, what will be taught and the competencies that students must be mastered. At the design stage, researchers designed learning device to be developed based on the results of previous analyzes in the form of RPP, teaching materials and assessment instruments as well as collecting references. The last stage, the development stage is the stage of creating the product design into a product that is ready to be implemented, at this stage a product validation instrument used to validate learning device is also arranged. The data collection technique was carried out by collecting data on the results of RPP, teaching materials and assessment instruments validation by four experts which was carried out at the development stage. The results showed that the score given by the validator to the RPP was 3.45 on the â€œvalidâ€ category, the score given to the teaching materials was 3.52 on the very â€œvalidâ€ category and the score given to the assessment instrument was 3.45 on the â€œvalidâ€ category. Based on the research results, it can be concluded that the learning device developed are suitable for use.